2015
DOI: 10.1016/j.celrep.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-B Receptor Activation in Astrocytes Regulates the Rate of Oligodendrocyte Regeneration during Remyelination

Abstract: Reactive astrogliosis is an essential and ubiquitous response to CNS injury, but in some cases, aberrant activation of astrocytes and their release of inhibitory signaling molecules can impair endogenous neural repair processes. Our lab previously identified a secreted intercellular signaling molecule, called endothelin-1 (ET-1), which is expressed at high levels by reactive astrocytes in multiple sclerosis (MS) lesions and limits repair by delaying oligodendrocyte progenitor cell (OPC) maturation. However, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…The same authors also reported high levels of immunoreactive ET-1 in spinal cord-localized inflammatory and neuroglial cells [31]. These observations are of relevance considering that Hammond et al (2014) have recently shown that ET-1 is a negative regulator of oligodendrocyte progenitor cell-dependent repair of demyelinated lesions [32]. In support of the latter observation, myelin contents were, in the present study, found to be higher in naive and even one week after EAE immunized mMCP-4 KO mice than in their WT congeners.…”
Section: Discussionmentioning
confidence: 87%
“…The same authors also reported high levels of immunoreactive ET-1 in spinal cord-localized inflammatory and neuroglial cells [31]. These observations are of relevance considering that Hammond et al (2014) have recently shown that ET-1 is a negative regulator of oligodendrocyte progenitor cell-dependent repair of demyelinated lesions [32]. In support of the latter observation, myelin contents were, in the present study, found to be higher in naive and even one week after EAE immunized mMCP-4 KO mice than in their WT congeners.…”
Section: Discussionmentioning
confidence: 87%
“…Our laboratory recently characterized a protein secreted by reactive astrocytes, endothelin-1 (ET-1), as a negative regulator of NG2 glial differentiation and functional remyelination 56,57 . Blocking ET-1 signaling by either pharmacological or genetic approaches enhances maturation of NG2 glia into oligodendrocytes after focal demyelination of the corpus callosum.…”
Section: Is the Glial Scar Inhibitory Or Beneficial To Regeneration?mentioning
confidence: 99%
“…In addition to these OPC-directed drugs, several experimental compounds have been described to trigger signaling pathways modulating oligodendrogenesis. The endothelin (ET) receptor antagonist BQ788 was demonstrated to block endothelin-B receptor activation on astrocytes, thereby rescuing oligodendrogenesis and promoting remyelination [133]. The flavonoid molecule quercetin leads to enhanced oligodendrogenesis and remyelination in several ways, as it suppresses Notch signaling by inhibiting Îł-secretase activity and disrupts the binding of ÎČ-catenin to TCF4 [134].…”
Section: Regulators Of Glia Cell Fate: Avenues To Adjust Aberrant Whimentioning
confidence: 99%